Voter Turnout Trends in India: A Critical Analysis - Mahendra A. C. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
This article examines the fluctuating trends in voter turnout in India from the first general elections in 1951-52 to the present, revealing both progress and persistent challenges. Despite a growing electorate and sustained efforts by the Election Commission of India (ECI) to encourage voter participation, turnout has remained relatively low, seldom crossing 65%. Through a critical analysis, the article delves into key issues such as regional disparities—especially the persistently low turnout in Jammu & Kashmir—gender-based voting gaps, and the divergence in participation between state and national elections. The comparison of India’s voter turnout with other democracies in South Asia underscores the systemic barriers to political engagement, including political apathy and logistical challenges. To strengthen democratic participation, the article argues for a multifaceted approach that addresses these deeper socio-political factors alongside continued electoral reforms.